The need for robust characterization of nanomaterials for nanomedicine applications - Morteza Mahmoudi (Nature Communications, 2021)
Robust and precise characterization of the interactions between nanoengineered materials and biosystems is vital for the development of safe, efficient diagnostic and therapeutic nanomedicines. This comment discusses the key aspects of nanoparticle characteristics affecting the interpretation of nano-bio interface data.